Pemberdayaan Petani melalui Penerapan Teknologi Hemat Energi pada Pembuatan Tepung Ganyong di Kabupaten Alor - Didiana Yanuarita Molebila; Imanuel Chr Mauko; Emirensiana Latuan (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The issue of stunting is a serious concern in the NTT region, including the Alor district. Empowering farmers in cultivating crops that support food diversification in dealing with stunting is a priority for the government's program. The Timau-Letluk Farmer Group in Lippang Village is one of the locations for empowering farmers through the cultivation of Canna (Banana Tanah) plants. Canna with the mineral content of calcium, phosphorus and iron can be an alternative food, as well as a solution for treating stunting. However, the processing of canna as a food source is still limited manually, and there is no touch of technology for processing canna tubers into good and nutritious canna flour, accompanied by the unavailability of electric power for the penepung machine. Therefore, the Tribuana Kalabahi University Service Team through the Community Creativity Program has answered partners' problems with the implementation of a 3 kW capacity Solar Power Plant (PLTS) system that is capable of driving a slurry machine with a production capacity of 50 kg/hour and 750 W power as a support in canna flour production. This activity was carried out to empower farmers to take advantage of agricultural potential to fulfill food needs, which was carried out through training in making canna flour and calculating their business to increase the economic welfare of farmers in Lippang Village, Alor Regency.